(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In this project analysis and design of a G+14 RC building is done by introducing the floating column in different conditions such as internal floating column, external floating column and alternate level floating column for determining parameter like displacement, forces and moments is done by using ETABS software. Also conclusion is carried out on the basis of following ways. Significant outcome of the study includes, provision of Internal and External floating columns increases the torsion values at all floors and provision of alternate level floating column there is reduction in torsion value. Provision of Internal floating columns Alternate floor floating columns may increase displacement at various nodes. Introduction of floating column increases torsion in beam at all floors for all zones. The quantity of steel and concrete gets increase as compared to the individual cases due to floating column so floating column may be provided at appropriate places as per requirement of the plan.